The Application of Maintenance Functions in The Human Resources Management of Islamic Financial Institutions - Arik Putri Lestari, Yosy (Institut Agama Islam Negeri Ponorogo, 2023)
Sharia Savings and Loan Cooperatives are unique in that they must balance their business principles with high and volatile work demands. The care function of human resource management is an essential aspect of ensuring employee well-being and job satisfaction within organizations, including sharia savings and loan cooperatives. This study specifically focuses on examining the application of maintenance functions at KSP BMT Surya Abadi Jenangan Ponorogo, an esteemed Islamic financial institution that has experienced rapid development in Indonesia and has contributed to economic improvement through its diverse financing products. This research aims to provide valuable insights into the organization's practices and contribute to the broader understanding of human resources management in Islamic institutions and ultimately improve the quality of their workforce and service performance. Through a comprehensive analysis, this study has illustrated the practices carried out by the organization in maintaining employee welfare and retention. KSP BMT SURYA Abadi Jenangan Ponorogo demonstrates efforts in prioritizing employee welfare and retention, with notable aspects including occupational health and safety, communication, and human resource welfare programs, although improvements are needed, particularly in the area of occupational health and safety.